Panorama Konstantynopola w Liber chronicarum Hartmanna Schedla (1493). Miasto idealne – memoria chrześcijaństwa - Mazurczak, Urszula (Vox Patrum, 2018)
The historical research of the illustrated Nuremberg Chronicle [Schedelsche Weltchronik (English: Schedel’s World Chronicle)] of Hartmann Schedel comprises the complex historical knowledge about numerous woodcuts which present views of various cities important in the world’s history, e.g. Jerusalem, Constantinople, or the European ones such as: Rome, some Italian, German or Polish cities e.g. Wrocław and Cracow; some Hungarian and some Czech Republic cities. Researchers have made a serious study to recognize certain constructions in the woodcuts; they indicated the conservative and contractual architecture, the existing places and the unrealistic (non-existent) places. The results show that there is a common detail in all the views – the defensive wall round each of the described cities. However, in reality, it may not have existed in some cities during the lifetime of the authors of the woodcuts. As for some further details: behind the walls we can see feudal castles on the hills shown as strongholds. Within the defensive walls there are numerous buildings with many towers typical for the Middle Ages and true-to-life in certain ways of building the cities. Schematically drawn buildings surrounded by the ring of defensive walls indicate that the author used certain patterns based on the previously created panoramic views. This article is an attempt of making analogical comparisons of the cities in medieval painting. The Author of the article presents Roman mosaics and the miniature painting e.g. the ones created in the scriptorium in Reichenau. Since the beginning of 14th century Italian painters such as: Duccio di Buoninsegna, Giotto di Bondone, Simone Martini and Ambrogio Lorenzetti painted parts of the cities or the entire monumental panoramas in various compositions and with various meanings. One defining rule in this painting concerned the definitions of the cities given by Saint Isidore of Seville, based on the rules which he knew from the antique tradition. These are: urbs – the cities full of architecture and buildings but uninhabited or civita – the city, the living space of the human life, build-up space, engaged according to the law, kind of work and social hierarchy. The tradition of both ways of describing the city is rooted in Italy. This article indicates the particular meaning of Italian painting in distributing the image of the city – as the votive offering. The research conducted by Chiara Frugoni and others indicated the meaning of the city images in the painting of various forms of panegyrics created in high praise of cities, known as laude (Lat.). We can find the examples of them rooted in the Roman tradition of mosaics, e.g. in San Apollinare Nuovo in Ravenna. They present both palatium and civitas. The medieval Italian painting, especially the panel painting, presents the city structure models which are uninhabited and deprived of any signs of everyday life. The models of cities – urbs, are presented as votive offerings devoted to their patron saints, especially to Virgin Mary. The city shaped as oval or sinusoidal rings surrounded by the defensive walls resembled a container filled with buildings. Only few of them reflected the existing cities and could mainly be identified thanks to the inscriptions. The most characteristic examples were: the fresco of Taddeo di Bartolo in Palazzo Publico in Siena, which presented the Dominican Order friar Ambrogio Sansedoni holding the model of his city – Siena, with its most recognizable building - the Cathedral dedicated to the Assumption of Mary. The same painter, referred to as the master painter of the views of the cities as the votive offerings, painted the Saint Antilla with the model of Montepulciano in the painting from 1401 for the Cathedral devoted to the Assumption of Mary in Montepulciano. In the painting made by T. di Bartolo, the bishop of the city of Gimignano, Saint Gimignano, presents the city in the shape of a round lens surrounded by defence walls with numerous church towers and the feudal headquarters characteristic for the city. His dummer of the city is pyramidally-structured, the hills are mounted on the steep slopes reflecting the analogy to the topography of the city. We can also find the texts of songs, laude (Lat.) and panegyrics created in honour of the cities and their rulers, e.g. the texts in honour of Milan, Bonvesin for La Riva, known in Europe at that time. The city – Arcadia (utopia) in the modern style. Hartman Schedel, as a bibliophile and a scholar, knew the texts of medieval writers and Italian art but, as an ambitious humanist, he could not disregard the latest, contemporary trends of Renaissance which were coming from Nuremberg and from Italian cities. The views of Arcadia – the utopian city, were rapidly developing, as they were of great importance for the rich recipient in the beginning of the modern era overwhelmed by the early capitalism. It was then when the two opposites were combined – the shepherd and the knight, the Greek Arcadia with the medieval city. The reception of Virgil’s Arcadia in the medieval literature and art was being developed again in the elite circles at the end of 15th century. The cultural meaning of the historical loci, the Greek places of the ancient history and the memory of Christianity constituted the essence of historicism in the Renaissance at the courts of the Comnenos and of the Palaiologos dynasty, which inspired the Renaissance of the Latin culture circle. The pastoral idleness concept came from Venice where Virgil’s books were published in print in 1470, the books of Ovid: Fasti and Metamorphoses were published in 1497 and Sannazaro’s Arcadia was published in 1502, previously distributed in his handwriting since 1480. Literature topics presented the historical works as memoria, both ancient and Christian, composed into the images. The city maps drawn by Hartmann Schedel, the doctor and humanist from Nurnberg, refer to the medieval images of urbs, the woodcuts with the cities, known to the author from the Italian painting of the greatest masters of the Trecenta period. As a humanist he knew the literature of the Renaissance of Florence and Venice with the Arcadian themes of both the Greek and the Roman tradition. The view of Constantinople in the context of the contemporary political situation, is presented in a series of monuments of architecture, with columns and defensive walls, which reminded of the history of the city from its greatest time of Constantine the Great, Justinian I and the Comnenus dynasty. Schedel’s work of art is the sum of the knowledge written down or painted. It is also the result of the experiments of new technology. It is possible that Schedel was inspired by the hymns, laude, written by Psellos in honour of Constantinople in his elaborate ecphrases as the panegyrics for the rulers of the Greek dynasty – the Macedonians. Already in that time, the Greek ideal of beauty was reborn, both in literature and in fine arts. The illustrated History of the World presented in Schedel’s woodcuts is given to the recipients who are educated and to those who are anonymous, in the spirit of the new anthropology. It results from the nature of the woodcut reproduction, that is from the way of copying the same images. The artist must have strived to gain the recipients for his works as the woodcuts were created both in Latin and in German. The collected views were supposed to transfer historical, biblical and mythological knowledge in the new way of communication.